Religiusitas Dan Kualitas Produk Terhadap Minat Beli Produk Wardah Di Kota Bima - Miratunnisa Miratunnisa; Irma Mardian; Ita Purnama (Universitas 45 Surabaya, 2023)
Indonesia is a country that is based on Pancasila in the foundations of its life. One of the Pancasila precepts is Belief in One Almighty God, which in everyday life religiosity is very evident in the behavior of Indonesian people. One of the reflections of this first sila behavior in everyday life is the consideration of consumers in choosing products to be consumed based on their beliefs. Religiosity is an inner relationship between humans and God that can affect their lives. The inner relationship between humans and God in everyday life such as carrying out worship or prayer rituals (Alfiani, 2013). In relation to worship, in order to meet human needs, especially for women, recently consumer awareness regarding halal and safe cosmetic products has begun to increase. According to Kottler in Abzari, et al (2014) buying interest is consumer behavior where consumers have a desire to choose and consume a product. Purchase intention arises from products and attributes offered to the market for attention, acquisition, use or consumption that might satisfy a want or need. Each cosmetic product offers various advantages such as quality, features and product design. With the increasing number of cosmetic products circulating in Indonesia, it results in various considerations for the public in making purchasing decisions. Purchase decisions arise because of consumer attitudes towards an object or product consumer confidence in product quality. Kottler and Keller (2016) state that product quality is a product's ability to perform its functions, this ability includes durability, reliability, accuracy obtained as a whole. The needs of women are slightly different from men, for women appearance is very important because women always want to look beautiful in front of other people. Apart from the need for food, drink and clothing, cosmetics are a necessity that cannot be ignored for women today. Each cosmetic product offers various advantages such as quality, features and product design. With more and more variants of cosmetic and skin care products circulating in Indonesia, this raises various considerations for the public in making purchasing decisions.